ENGLISH-FRENCH TRANSLATION: PROBLEMS AND SOLUTIONS (Konferensiyalar | Conferences, 2023)
French translation and localization are essential for any company or organization aiming to expand because of its extensive reach and profound roots, particularly if the focus is on Europe. It is obvious that high-quality, on-brand translation and localization are required, as the majority of consumers claim that having access to information about a product or service in their native tongue can be more significant than pricing. Even though French is a language that is spoken by many people, there are still some translation issues that come up. We will go over a few of these issues and their fixes in this paper.